2011
DOI: 10.4236/ss.2011.25061
|View full text |Cite
|
Sign up to set email alerts
|

Midline Prostatic Cysts Presenting with Chronic Prostatitis or Secondary Infertility and Minimally Invasive Treatment: Endoscopic or Laparoscopic Approach?

Abstract: Backgrounds: Surgical interventions especially minimally invasive treatments are recommended for symptomatic midline prostatic cysts. The endoscopic unroofing of cysts close to urethra is easy and simple, but it has little effect on the large cysts and cysts lying deeply, in contrast with the laparoscopic approach. Therefore, the selection of minimally invasive therapeutic approaches is important. The aim of this study is to describe our experience in the diagnosis and selection of minimally invasive treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…However, transurethral techniques have shown no recurrence of MPCs during follow-up. Zhang et al [18] also recommended transurethral unroofing of small prostatic cysts that are close to the urethra or bladder cavity because of its simplicity, outcomes, low complication rate and short recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…However, transurethral techniques have shown no recurrence of MPCs during follow-up. Zhang et al [18] also recommended transurethral unroofing of small prostatic cysts that are close to the urethra or bladder cavity because of its simplicity, outcomes, low complication rate and short recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic cyst is a rare disease with uncertain origin [1][2][3][4], which needs to be differentiated from prostatic neoplastic masses, prostatic non neoplastic masses, periprostatic neoplastic masses, periprostatic neoplastic masses and cyst of seminal vesicle. Most of prostatic cysts are small and located laterally without spermatozoa [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…14 An analysis on 34 patients with symptomatic prostatic cysts by Tambo et al 7 revealed that 40% of the patients suffered from obstructive urinary symptoms, 33% from urinary retention, 9% from urodynia and 6% from infertility. 20 also recommended transurethral unroofing of small prostatic cysts (< 2 cm x 2 cm) that are close to the bladder cavity or urethra, because of the simplicity of the technique, the low risk of complications and the shorter convalescence period.…”
Section: -5mentioning
confidence: 99%